(untitled) (Islamic Sciences Journal, 2023)
Banks provide their customers with a variety of services, either to finance their projects, or to satisfy their needs. Islamic banks are distinguished from commercial banks in their choice of financial services and transactions that satisfy those needs, and provide capital for projects in accordance with Islamic law. Among these transactions are: (Islamic instruments) that can be applied in Iraqi society to meet the need for transportation, housing and academic study.going to an intellectual, doctrinal and moral decline, Allah forbid.